Challenges and prospects of selected controlled environment agriculture (cea) structures in ibadan metropolis (2014)
Over the years, the concepts of climate change and global warming has been continually studied and its expected effects have been well documented. These environmental issues have reduced the effectiveness of open field agriculture and as such other cultivation methods had to be devised; controlled environment agriculture is one of such methods. This survey was conducted in three selected controlled environment agriculture structures within Ibadan City to determine the challenges and some environmental factors affecting the use of controlled environment agriculture structures in this area. The research methodology used included visual inspection, field measurements and personal interviews. The results showed that that only a few of the factors that could be controlled were being controlled in all the locations visited and that controlled environment agriculture is still in the research stage in Ibadan particularly when talking about the crop cultivation aspect. Other challenges in its usage included inadequate water supply, epileptic power supply, lack of adequate ventilation, litter management, egg cannibalism, feed management and poor maintenance. It was suggested that the controlled environment agriculture structures management should provide alternative power and also introduce devices that will aid air and heat movement as well as temperature control. Reuse of litter for manure and proper maintenance were also recommended